Evaluation of factors affecting aquafaba rheological and thermal properties. (October 2020) - Alsalman, Fatemah B.; Tulbek, Mehmet; Nickerson, Michael; Ramaswamy, Hosahalli S.
Abstract: Aquafaba is the residual water left after cooking of chickpeas, which contains many water soluble proteins and complex carbohydrates, and commercially used in cakes and dessert fillings to replace egg-white. The effectiveness of aquafaba to replace egg-white as an emulsifier depends on several of its functionalities and therefore this study was aimed at evaluating its rheological (flow, viscosity, gelling ability and rigidity) and thermal (denaturation and gelatinization) properties. An I-optimal combined mixture-process design was used to optimize rheological and thermal properties of freshly prepared aquafaba under variable cooking conditions. The target was to maximize the consistency coefficient and oscillatory elastic modulus, and minimize the associated enthalpy and tan δ . The results showed that, chickpeas to water ratio and cooking time had significant effects on the responses. Polynomial mathematical models were developed for all nine responses. Optimal conditions were chickpea: water ratio of 2:3 and cooking time of 60 min which resulting in an overall desirability value of 0.96, which was confirmed through validation experiments. Highlights: Aquafaba quality is influenced by the cooking process and chickpea proportion. Rheological and thermal properties have functional influence on aquafaba quality. Study provides optimization opportunity of aquafaba production and functionality. Study identifies conditions optimizing rheological properties of aquafaba.